CLINICAL CHARACTERISTICS, CAUSALITY, AND EVALUATION OF EYE LID LACERATION SURGERY IN KARIADI GENERAL HOSPITAL, SEMARANG - Lazuardi, Nizar Arif; Nugroho, Trilaksana (Majalah Oftalmologi Indonesia, 2023)
Introduction and Objective: Eyelid lacerations appear to be understudied in terms of adequate epidemiological research among all injury sites. The aim of this study was to assess the etiological characteristics, and evaluation of eyelid laceration surgery in Kariadi General Hospital. Method: In a observational analytic study with retrospective design, 89 cases of isolated traumatic eyelid laceration were consecutively studied and its epidemiology, etiology and the surgery were evaluated. All patients who underwent lid surgery between March 2021 and March 2023 were included. The data is analyzed to determine the features and the connection between the resulting frequency and the variables that were collected. Result: This study enrolled 89 patients with 66 (74.2%) males and 23 (25.8%) females. The largest age group in this study was 16–50 years old, with 53 patients (59.6%). With respect to the regio of laceration, medial laceration regio was reported in 69 patients (77.5%), central laceration regio was reported in 8 patients (9%), and lateral laceration regio was reported in 12 patients (13.5%). Based on the grade, 68 patients (76.5%) had full-thickness lacerations, and 21 patients (23.6%) had lamellar lacerations. Conclusion: Male tend to have a higher incidence rate than female. The highest age range is among adolescents and young adults.